2006
DOI: 10.1038/sj.onc.1209583
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-1 expression is activated in vivo by Ets-1 through palindromic head-to-head Ets binding sites present in the promoter

Abstract: Regulation of the gene expression of Stromelysin-1 (matrix metalloproteinase-3), a member of the matrix metalloproteinase family, is critical for tissue homeostasis. The Stromelysin-1 promoter is known to be transactivated by Ets proteins through palindromic headto-head Ets binding sites (EBS), an unusual configuration among metalloproteinase promoters. Patterns of increased co-expression of Stromelysin-1 and Ets-1 genes have been observed in pathological processes such as rheumatoid arthritis, glomerulonephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…However, several TF knockdowns that successfully degraded laminin in our model system have been shown to promote basement membrane remodeling in other systems. Previous studies have demonstrated that ets1 directly upregulates mmp1 (collagenase 1), mmp3 (stromelysin 1), mmp9 (gelatinase B) and mmp13 (collagenase 3) (Westermarck et al, 1997;Baillat et al, 2006;Ghosh et al, 2012). Snail and twist are also associated with upregulated MMPs (Sánchez-Tilló et al, 2012), although this evidence is indirect.…”
Section: Research Articlementioning
confidence: 82%
“…However, several TF knockdowns that successfully degraded laminin in our model system have been shown to promote basement membrane remodeling in other systems. Previous studies have demonstrated that ets1 directly upregulates mmp1 (collagenase 1), mmp3 (stromelysin 1), mmp9 (gelatinase B) and mmp13 (collagenase 3) (Westermarck et al, 1997;Baillat et al, 2006;Ghosh et al, 2012). Snail and twist are also associated with upregulated MMPs (Sánchez-Tilló et al, 2012), although this evidence is indirect.…”
Section: Research Articlementioning
confidence: 82%
“…Previous studies on TNFa-dependent MMP-3 activation have identified Ets-1 and NFjB as the main effectors of gene expression in synovial fibroblastic cells 16 and monocyte-derived macrophages. 17 In this report, we have made similar observations on MMP-3 induction in the T98G cells upon TNFa treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] It has been shown that Ets-1 and NFjB are the main transcription factors in controlling MMP-3 gene expression inducible by TNFa in fibroblasts and macrophages. 16,17 To elucidate the underlying mechanisms by which IFNg suppresses TNFa-induced MMP-3 expression, we investigated the effects of IFNg on the DNA-binding activity of Ets-1, NFjB and AP-1 to their respective enhancer elements. Results of EMSA suggested that TNFa activated DNA-binding of Ets-1 and NFjB to their respective oligodeoxynucleotide enhancer sequences (Fig.…”
Section: Ifnc Blocks Dna-binding Activity Of Tnfa-activated Ets-1 Andmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (Baillat et al, 2006) using (1) 30 mg of total cell lysate proteins or (2) 25 ml of total cell lysates in the case of reporter gene assays, which were boiled in Laemmli buffer (50 mM Tris (pH 6.8), 2% sodium dodecyl sulfate, 5% b-mercaptoethanol, 10% glycerol, 0.1% bromophenol blue). Primary antibodies used (Santa Cruz Biotechnology, Santa Cruz, CA, USA) were the C-20 anti-Ets-1, C-20 anti-Ets-2, 16 anti-PEA3, C-14 anti-Erk-2, H-79 anti-cJun and H-125 anti-cFos.…”
Section: Western Blot Analysismentioning
confidence: 99%